Simultaneous vehicular location and velocity detection towards 6G integrated communication and sensing - Bingpeng ZHOU; Shanshan MA (Tongxin xuebao)
Joint vehicle location and velocity estimation algorithm was proposed for 6G millimeter wave integrated communication and sensing (ICAS), which was challenging due to random channel fading and multipath interference.A novel receiver state sensing (RSS) algorithm was proposed to simultaneously estimate vehicle (receiver) location and velocity, in conjunction with reflection channel estimation.Moreover, a novel multi-carrier Doppler calibration scheme was developed to reduce the disturbance of Doppler effect on RSS performance via frequency shift compensation.The impact of system parameters, e.g., signal bandwidth, the number of transceiver antenna and sub-carriers, on RSS performance was evaluated as well.It was verified by simulations that the proposed RSS algorithm outperformed state-of-the-art baseline methods due to the employed problem-specific system design.In addition, it was shown by simulations that the achieved RSS error was reduced with the increasing of sub-carrier frequency, the number of transceiver antennas and sub-carriers, and it was increased with the increasing distance between base station and vehicle receiver.Particularly, the vehicle location estimation accuracy was increasing with system bandwidth, but it was invariant with central carrier frequency, since only baseband features of received signal were employed for vehicle localization.In contrast, the vehicle velocity detection accuracy was increasing with central carrier frequency, yet it was insensitive to system bandwidth, given the fixed number of sub-carriers.